Achieving SDGs: The Role of Independent Commissioners, Managerial Ownership, Audit Committees, and Profitability in the Manufacturing Industry - Wahyuni Fitri; Nurmalasari; Ainy Rintan Nuzul; Rifandi Muhamad (SHS Web of Conferences)
This research examines the influence of Independent Commissioners, Managerial Ownership, Audit Committees, and Profitability on the disclosure of Sustainable Development Goals (SDGs) in manufacturing companies in Indonesia. This secondary research uses quantitative data on 84 manufacturing companies that report sustainability reports from 2020 to 2022, with a total sample of 252. Independent commissioners are proxied by the ratio of the number of independent commissioners to total commissioners, managerial ownership is measured using the managerial ownership ratio, audit committees are measured using the number of audit committees, profitability is measured using return on assets, and SDGs disclosure is measured using the number of SDGs objectives. SPSS was used for hypothesis testing in this research. The results show that independent commissioners, managerial ownership, audit committees, and profitability have an impact on SDG disclosure.